Evaluating the content and quality of cognitive-behavioural therapy case conceptualisations - Haarhoff BA; Flett RA; Gibson KL (New Zealand Psychological Society, 2011)
Whilst case conceptualisation (CC) is considered a key Cognitive-Behaviour Therapy (CBT) competency, assessment and evaluation of the content and quality of CBT CC skills is not generally part of CBT training. In this paper, the content and quality of CCs produced by novice CBT clinicians was evaluated. Twenty-six novice CBT clinicians constructed CCs based on four clinical case vignettes. The content and quality of the CCs was evaluated using three rating scales, the Case Formulation Content Coding method, the Fothergill and Kuyken Quality of Cognitive-Therapy Case Formulation rating scale, and the CBT CC rating scale and benchmark conceptualisations. Descriptive statistical analysis of content displayed consistent distribution of subcategories of clinical information included, or omitted in the CCs. Underlying psychological mechanisms were emphasised. Information concerning biological, socio-cultural, protective factors, and the therapeutic relationship were generally omitted. As far as quality was concerned, between 50% - 61% of participants produced 'good-enough' CBT CCs. The consistent pattern of clinical information evidenced in the participants' CCs highlighted strengths and weaknesses which have implications for improving training in CC CBT competency.
Keywords: 1701 Psychology; 1702 Cognitive Sciences